The Development of MOSIRI (Geometry Transformation Module) for High School Students - Gianto, Emeralda Kislew Andhika; Mampouw, Helti Lygia; Setyadi, Danang (Al-Jabar: Jurnal Pendidikan Matematika, 2018)
Geometry transformation is one of the mathematics learning materials that are very closely related to everyday life but has many formulas that make it difficult for students, especially high school students to understand it. Seeing the importance of geometric transformation and difficulties experienced by students, the development of a geometry transformation module was carried out which was able to eliminate difficulties in studying and understanding the geometric transformation. This research is development research with ADDIE development modelto produce a valid, practical, and effectivemodule on geometric transformation. The module is aimed at helping high school students to understand the relevance of geometry transformation to reality and how to solve it. This module is declared valid in terms of media and material aspects with an average validity score of 3.7 (valid) for material aspects and 4 (valid) for media aspect. This module was tested on 10 ten grade high school students and is declared practical based on the indicators of the media practicality sheet. In addition, with the help of a test sheet, it can be seen that this module is able to improve learning outcomes. This can be seen from the results of a paired simple test which shows a significance value of 0,000 () which means that this module is able to provide differences or improve students’ learning outcomes based on the average pretest score which is 51 to 88 of theaverage posttest score. Based on the three tests, this module was declared valid, practical, and effective to be used in geometric transformation material for high school students.